2010
DOI: 10.1007/s00280-010-1343-8
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase II study of PX-12, an inhibitor of thioredoxin in patients with advanced cancer of the pancreas following progression after a gemcitabine-containing combination

Abstract: Due to the lack of significant antitumor activity and unexpectedly low baseline Trx-1 levels, the study was terminated early. PX-12 does not appear to be active in unselected patients with previously treated APC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
79
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 31 publications
0
79
0
1
Order By: Relevance
“…To the best of our knowledge, no combination studies with TrxR1 inhibitors and standard chemotherapy agents have been reported using PDAC cell lines. A randomised clinical study of PDAC patients with advanced disease treated with thioredoxin inhibitor monotherapy failed to demonstrate improved outcomes, however considerable methodological issues may have obscured potential benefits of inhibiting this antioxidant system (Ramanathan et al, 2011). Interestingly, TrxR1 may also regulate Nrf2 activation (Cebula et al, 2015).…”
Section: The Effects Of Suppressing Nrf2 Compared To Nrf2/are Effectomentioning
confidence: 99%
“…To the best of our knowledge, no combination studies with TrxR1 inhibitors and standard chemotherapy agents have been reported using PDAC cell lines. A randomised clinical study of PDAC patients with advanced disease treated with thioredoxin inhibitor monotherapy failed to demonstrate improved outcomes, however considerable methodological issues may have obscured potential benefits of inhibiting this antioxidant system (Ramanathan et al, 2011). Interestingly, TrxR1 may also regulate Nrf2 activation (Cebula et al, 2015).…”
Section: The Effects Of Suppressing Nrf2 Compared To Nrf2/are Effectomentioning
confidence: 99%
“…Pharmacokinetic studies during a recent PX-12 phase I clinical trial revealed that PX-12 given at 400 mg/m 2 /d for 72 hours is safe to administer to patients (49). However, to determine whether PX-12 exhibits cytotoxicity to immune cells and cornea-specific…”
Section: Fungal Thioredoxin Mediates Resistance To Human Neutrophilsmentioning
confidence: 99%
“…A patient with appendiceal adenocarcinoma had a minor response of 322 days (79). PX-12 was also investigated in a Phase II trial as a 3-h infusion at two dose levels in patients with previously treated advanced pancreatic cancer (78). Plasma Trx-1 levels were found elevated in only 3 of 28 (11%) patients screened for study.…”
mentioning
confidence: 99%